Evaluation isometric and isokinetic of trunk flexor and extensor muscles with isokinetic dynamometer: A systematic review - Estrázulas, J. A.; Estrázulas, J. At.; de Jesus, Ke.; de Jesus, Ka.; da Silva, R. A.; Libardoni dos Santos, J. O. (Physical Therapy in Sport, 2020)
The evaluation of the trunk muscles using isokinetic dynamometer present high reliability. Peak torque is an important variable. The evaluation parameters are different between sitting and orthostatic position. Objective: To systematically review the literature analyzing the reliability and characteristics of the protocols of isokinetic and isometric evaluation of the trunk flexor and extensor muscles with isokinetic dynamometer.